Republicanism and the American Gothic - Michaud, Marilyn (Gothic literary studies., 2009)
This book is a comparative study of British and American literature and culture in the 1790s and 1950s. It explores the republican tradition of the British Enlightenment and the effect of its translation and migration to the American colonies.